2000
DOI: 10.1002/(sici)1521-3765(20000417)6:8<1318::aid-chem1318>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Series of Copolymers Containing 2,5-Dicyano-1,4-phenylenevinylene-Synthetic Tuning of the HOMO and LUMO Energy Levels of Conjugated Polymers

Abstract: A series of copolymers of 2,5-dicyano-1,4-phenylenevinylene and 2-methoxy-5-(2'-ethylhexyloxy)-1,4-phenylenevinylene were synthesized by Wittig reaction. The HOMO and LUMO energy levels of copolymers can be easily tuned by controlling the feed ratio of co-monomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…It was demonstrated that the introduction onto the PPV skeleton of units with different electron affinity, such as alkoxy electron-donating and cyano electron-withdrawing groups, can be used as a valuable strategy to modify and adjust the HOMO and LUMO energy levels of the materials, obtaining a better matching with the work function of metal electrodes in OLED devices, thus improving performances [56,57]. In this contest, fluorine atoms appeared very interesting as for electron-withdrawing functionalities.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that the introduction onto the PPV skeleton of units with different electron affinity, such as alkoxy electron-donating and cyano electron-withdrawing groups, can be used as a valuable strategy to modify and adjust the HOMO and LUMO energy levels of the materials, obtaining a better matching with the work function of metal electrodes in OLED devices, thus improving performances [56,57]. In this contest, fluorine atoms appeared very interesting as for electron-withdrawing functionalities.…”
Section: Resultsmentioning
confidence: 99%
“…The following starting materials were prepared according to literature methods: 1,4-diiodo-2,5-dihexylbenzene 37 and 2,5-dicyano-1,4-bis(bromomethyl)benzene. 38 4-Butyl-N,N-diphenyl-aniline (1). To a solution of tris-(dibenzylideneacetone)dipalladium (Pd 2 dba 3 ) (1.099 g, 1.2 mmol) and bis(diphenylphosphino)ferrocene (dppf) (0.998 g, 1.8 mmol) in toluene (180 mL) under nitrogen atmosphere was added bromobenzene (28.264 g, 180 mmol) and the resultant solution was stirred for 10 min at ambient temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Because most conjugated polymers such as PPV are better suited for hole injection and transport compared with electron injection and transport, the unsatisfactory quantum efficiency of OLEDs is attributed to the lower injection rate of electrons from the cathode into the polymer emissive layer. On the basis of the p-n diblock concept, Huang et al synthesized a conjugated polymer consisting of 2,2′-bipyridylenevinylene (BPyV) and 2-meth-oxy-5- The polymer can be changed from a typical hole-transport (HT) material to a typical electron-transport (ET) material by varying the monomer feed ratio [24]. Quantum chemical calculations and previous research have demonstrated that introducing an electron-withdrawing group onto either the aryl ring or the vinyl group of PPV can lower both the HOMO and LUMO energy levels of the polymer, thus improving electron injection.…”
Section: Synthesizing Linear P-n Diblock Polymers To Adjust the Energmentioning
confidence: 99%